2023
DOI: 10.3390/su15064820
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge: A Factor for Acceptance of Insects as Food

Abstract: The role that insects will play in a healthier and more sustainable diet has been highlighted in the last years, at the European level. In future, due to environmental concerns and population growth, eating insects might be a solution for many problems. However, populations without the tradition of eating insects are still reluctant in accepting such a food as part of their diet. The present observational study highlights some factors that are influencing the acceptance of insects as food in Romania, in 2022. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
(56 reference statements)
0
2
0
1
Order By: Relevance
“…In order to promote edible insects more effectively and persuasively as future food, more knowledge is needed about the nutritional value of insects and the environmental advantages of entomophagy [33]. It is crucial to educate people about the health, environmental, and economic benefits of edible insects to introduce them as food in the future, as this can increase their willingness to do so [51,79,82,83]. The availability and variety of insect-based food products on the Polish market can also influence perceptions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to promote edible insects more effectively and persuasively as future food, more knowledge is needed about the nutritional value of insects and the environmental advantages of entomophagy [33]. It is crucial to educate people about the health, environmental, and economic benefits of edible insects to introduce them as food in the future, as this can increase their willingness to do so [51,79,82,83]. The availability and variety of insect-based food products on the Polish market can also influence perceptions.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, insect-based products seem to be more widely accepted than whole insects [73,79]. Certain products, such as insect powders (flours), bakery products, and protein bars, have improved their acceptance [77].…”
Section: Perceptions and Barriers To Consuming Insect-based Food Prod...mentioning
confidence: 99%
“…This work confirmed a higher average level of knowledge for Mexican and Lebanese participants, as well as differences among European countries, with Spanish and Polish participants being better informed about the nutritive value and health effects of EIs. Previous work has shown that knowledge is a valuable instrument for the acceptance of insects as food in communities where there is no tradition of eating insects [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the standpoint of sustainable development and environmental protection, breeding and processing insects is also associated with many environmental benefits as it, i.a., requires less area and smaller water consumption than conventional production, generates lower greenhouse gas emissions than mass production, and may use waste from the agri-food industry as inputs to produce food and feedstuffs, which further corresponds to the current trends of "zero waste" and "circular economy" [5,9,[34][35][36][37][38]. Beside the environmental aspect, insect production ensures a higher feed conversion ratio compared to the conventional animal production [23,[39][40][41]. The production of food containing insects is also economically viable.…”
Section: Introductionmentioning
confidence: 99%